Monitoring the Immune System in Critically Ill Patients (Review) - А. V. Stepanov; K. G. Shapovalov (Общая реаниматология)
Most patients with critical illness, regardless of the cause, develop activation of innate and adaptive immunity. This is often a critical process leading to organ dysfunction.The aim of the review is to systematize information on monitoring the immune system in critical illness for physicians of different specialties (anesthesiology and intensive care, surgery, general practice, obstetrics and gynecology).The review includes information from 83 recent national and international publications (mostly from 2023), available in the public domain and found by keyword search.We have summarized the current understanding of the relationship between infections and the human immune system, as well as the clinical application of traditional markers of immune status. We provided data on novel promising markers for the assessment of immunity in patients with various diseases.Limitations of the studies reviewed include the need for additional large-scale clinical trials of even the most promising markers, as well as a synthesis of the evidence for their performance. In addition, immune monitoring is likely to increase the cost of patient care, necessitating the development of more affordable research methods.Conclusion. Almost all disorders in critically ill patients are associated with changes in the immune system. Management of patients based on their immune profile requires determination of a personalized strategy for immune modulation, treatment, and prevention of infection. Advanced monitoring of immune system functions will contribute to the personalization of medicine, and the continuous development of biological technologies will allow to improve its methods.